2022
DOI: 10.3390/genes13122380
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Glyproline Peptides’ Activity through the Modulation of the Inflammatory and Neurosignaling Genetic Response Following Cerebral Ischemia–Reperfusion

Abstract: Glyprolines are Gly-Pro (GP)- or Pro-Gly (PG)-containing biogenic peptides. These peptides can act as neutrophil chemoattractants, or atheroprotective, anticoagulant, and neuroprotective agents. The Pro-Gly-Pro (PGP) tripeptide is an active factor of resistance to the biodegradation of peptide drugs. The synthetic Semax peptide, which includes Met-Glu-His-Phe (MEHF) fragments of adrenocorticotropic hormone and the C-terminal tripeptide PGP, serves as a neuroprotective drug for the treatment of ischemic stroke.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Nonetheless, this effect might not relate to the influence of PGP only. We have previously shown that the effect of PGP injections on the expression of inflammatory cluster genes was unlike the Semax effect 24 h after tMCAO [25]. Thus, the inflammatory-related genes were DEGs after Semax but non-DEGs after PGP administration under IR conditions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, this effect might not relate to the influence of PGP only. We have previously shown that the effect of PGP injections on the expression of inflammatory cluster genes was unlike the Semax effect 24 h after tMCAO [25]. Thus, the inflammatory-related genes were DEGs after Semax but non-DEGs after PGP administration under IR conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, Semax was associated with a correction to the gene expression patterns that are disrupted during cerebral ischemia 24 h after tMCAO. The genes in this pattern were grouped into an inflammatory cluster and a neurotransmitter cluster [24,25]. A number of Semax effects have also been demonstrated at the level of protein expression in the ischemic brain of rats [26].…”
Section: Introductionmentioning
confidence: 99%
“…Using real-time RT-PCR, we studied the effects of PGP and another PGP-containing the Pro-Gly-Pro-Leu (PGPL) peptide on the expression of a number of inflammatory cluster (IC) and neurotransmitter cluster (NC) genes in rat brain under transient MCAO. Then, we compared the studied peptide effects with the action of Semax under IR conditions [96,117]. Both PGP and PGPL peptides showed an effect dissimilar to the effects of Semax at 24 h after transient MCAO.…”
Section: Transcriptomic Analysis As a New Approach To Reveal The Mole...mentioning
confidence: 99%
“…The expression levels of these genes changed significantly after the corresponding peptide, compared to Semax administration. Based on the results of the analysis of gene expression under experimental conditions using bioinformatic approaches, a functional network was built that illustrates the spectra of common and unique effects of PGP, PGPL, and Semax peptides [117]. Thus, transcriptomic analysis, in addition to studying the molecular mechanisms of action of peptides, makes it possible to reveal the relationship between their chemical structure and possible effects at the genomic and functional levels.…”
Section: Transcriptomic Analysis As a New Approach To Reveal The Mole...mentioning
confidence: 99%